2018
DOI: 10.20896/saci.v5i3.292
|View full text |Cite
|
Sign up to set email alerts
|

Sanitation and Hygiene of Darjeeling City: A Crisis for Women and Adolescent Girls

Abstract: By the end of the Millennium Development Goal's target year, 2015, India had been declared as a country, which has made moderate progress in terms of improvement in basic sanitation provision for all. Yet open defecation is still a regular practice of a significant proportion of the population in both urban and rural areas. The Indian government has been trying to address this problem for the last three decades through different programmes. However, though the effort is laudable, in reality, the countrywide si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…According to the field survey, 32% of the households fails to have the toilet facilities within the premises of the house. This observation bear resonance to the research findings of Koner (2018) where she demonstrates the crisis faced by women and girls due to the lack of adequate sanitation facilities in Darjeeling town, West Bengal.…”
Section: Food Utilisationsupporting
confidence: 74%
“…According to the field survey, 32% of the households fails to have the toilet facilities within the premises of the house. This observation bear resonance to the research findings of Koner (2018) where she demonstrates the crisis faced by women and girls due to the lack of adequate sanitation facilities in Darjeeling town, West Bengal.…”
Section: Food Utilisationsupporting
confidence: 74%
“…Over the course of their reproductive lifespans, adolescent girls and women have increased and fluctuating water and sanitation-related requirements as compared to men, linked to menstruation, pregnancy (e.g., post-partum bleeding, miscarriage, stress urinary incontinence), and other common health conditions such as those that involve increased vaginal bleeding (e.g., uterine fibroids, endometriosis). Research has found that the challenges posed by long public lines or other situations causing anxiety related to the inconvenient access to safe and clean toilets outside their homes help to create, among girls and women, a range of coping mechanisms with potential health consequences, such as reducing their intake of liquids or food [29][30][31]. Although there is a need for more rigorous research on these associations, dehydration and regulating urination may increase risks for urinary tract infections and chronic constipation [32][33][34][35][36].…”
Section: Toilets and Healthmentioning
confidence: 99%
“…These observations bear resonance to the importance of Clean India or Swachh Bharat Abhiyan launched in 2014 by honourable Prime Minister of India, Mr Narendra Damodardas Modi (Bhattacharyya, 2014;Bhattacharyya and Pulla, 2019;Das,2018). One has to acknowledge that in the aftermath of the launch of the Swachh Bharat Abhiyan aimed at creating a clean and hygienic landscape by building 'basic hygiene and sanitation infrastructure' through the construction of toilets and complete elimination of open defecation (Bhattacharyya, 2014b;Bhattacharyya and Pulla, 2019;Das, 2018: 1;Koner, 2018). 1 "While the society has [gradually started] welcome[ing] these social initiatives, its reach and impact will perhaps take some time to reflect given India's geographical extent and bureaucratic challenges at both federal and sub-national level" (Das, 2018:1).…”
Section: Resultsmentioning
confidence: 99%
“…His life has been captured in 2018, motion picture, 'Padman', directed by R. Balki, and acted by Akshay Kumar, Sonam Kapoor and Radhika Apte. This picture is an excellent demonstration of how the villagers, whose social and cultural training are embedded in tacit taboo about menstruation (Koner, 2018) treated the pad man where he received vehement unacceptability from his society. Evidently, the cost of these napkins are almost one-third of the cost of commercial napkins.…”
Section: Introductionmentioning
confidence: 98%